2021
DOI: 10.3390/min11070739
|View full text |Cite
|
Sign up to set email alerts
|

Creation of Backfill Materials Based on Industrial Waste

Abstract: The possibility of replacing the traditional components of the filling mass with man-made waste and the need for the use of mechanical activation of the components of the filling composite in order to improve its rheological characteristics and the strength of the mass after solidification are proved. The demand for resource-reproducing technologies that allow the most complete use of the industrial mineral resource potential of the mining and processing enterprise, which will lead to a multiplicative ecologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…All these measures make it possible to reduce the conditional threshold of natural and man-made georesources involved in the development, to obtain an additional marketable product, and to dispose of man-made waste after deep processing [42][43][44]. In total, this will increase the financial efficiency of a mining [45][46][47] and processing enterprise [23,24,33,[48][49][50] and ensure high environmental safety. Even after introducing all these measures, we will still be far from circular economy and closed-loop that still seem to be a wishful thinking in the case of mineral processing.…”
Section: Comprehensive Utilization Of Georesources Through the Prism Of Environmental Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…All these measures make it possible to reduce the conditional threshold of natural and man-made georesources involved in the development, to obtain an additional marketable product, and to dispose of man-made waste after deep processing [42][43][44]. In total, this will increase the financial efficiency of a mining [45][46][47] and processing enterprise [23,24,33,[48][49][50] and ensure high environmental safety. Even after introducing all these measures, we will still be far from circular economy and closed-loop that still seem to be a wishful thinking in the case of mineral processing.…”
Section: Comprehensive Utilization Of Georesources Through the Prism Of Environmental Safetymentioning
confidence: 99%
“…In view of the decrease in the average useful component content of natural deposits and their comparability with anthropogenic formations in terms of volumes (Table 1) and the amount of useful components (Tables 2 and 3) in human-made accumulations, it is advisable to classify man-made formations as deposits [22]. Man-made waste from mining, processing, and metallurgical industries contains useful components and constitutes man-made georesources [23][24][25]. With an increase in consumer demand for extracted raw materials, it is necessary to increase the requirements for the completeness and complexity of the use of the mineral resource base, and to develop a new scientific and methodological approach to the broad recovery of mineral resources and their preservation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropogenic soils come in various forms, depending on the technology of their storage (dumping) and usage. At present, dumping (external and internal) is used to create landfills [15,16], heaps and earthwork structures [17][18][19] (e.g., road embankments, levees). Anthropogenic soils, as human-occupied layers, have also shaped the surface and subsoil in cities.…”
Section: Figurementioning
confidence: 99%
“…In order to meet this development keynote, a Minerals Special Issue recently focused on "Valorization of Metallurgical and Mining Residues and Wastes". Rybak et al [1], considering artificial wastes instead of traditional backfill components, indicated that resource-reproducing technologies allow mining and processing enterprises to make full use of industrial mineral resources, resulting in multiple ecological and economic effects. Bagani et al [2] discussed the possible use of nepheline syenite as a mine by-product in leaching alumina from azeotropic HCl solution.…”
Section: Introductionmentioning
confidence: 99%